Alternative splicing of the Anopheles gambiae nicotinic acetylcholine receptor, Agamalphabeta9, generates both alpha and beta subunits. - Jones, A; Buckingham, S; Brown, L; Sattelle, D (2009)
Nicotinic acetylcholine receptors (nAChRs) are the members of the cys-loop ligand-gated ion channel superfamily and are formed by five subunits arranged around a central ion channel. Each subunit is encoded by a separate gene and is classified as either alpha or non-alpha depending on the presence or absence, respectively, of two adjacent cysteine residues which are important for acetylcholine binding. Here, we report for the first time a single nAChR gene encoding both alpha and non-alpha subunits. Specifically, alternative splicing of the Anopheles gambiae nAChR subunit, previously called Agamalpha9 and renamed here Agamalphabeta9, generates two variants, one possessing the two cysteines (denoted Agamalphabeta9(alpha)) and the other lacking the cysteine doublet (Agamalphabeta9(beta)). Attempts to heterologously express functional nAChRs consisting of the Agamalphabeta9 splice variants in Xenopus laevis oocytes were unsuccessful. Our findings further characterise a potential target to control the malaria mosquito as well as provide insights into the diversification of nAChRs.